PERBANDINGAN PENGARUH PEMBERIAN ANALGETIK COX-2 DENGAN ASAM MEFENAMAT TERHADAP RASA NYERI PASCA ODONTEKTOMI (IMPAKSI KELAS 1, MOLAR 3 RAHANG BAWAH) - Dicky Kresnadi Rahmanto; Kuswartono Mulyo (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background: Sore is a common gripe and frightening experience for patients post odontectomyso patients requiredof proper and good treatment. Mefenamic acid analgesic drug effects can not always be achieved the maximum in comparison with the type of drug effects etoricoxib that can achieve maximum results with appropriate and well.Objective: To determine the effect of etoricoxib with analgesic mefenamic acid against sore odontectomy.Methods: This study is a quasi-experimental research design "post test only randomized controlled group design" with the double-blind technique. Samples were divided two groups where each group numbered 15, namely the treatment group receive analgesic drugs etoricoxib 90 mg and group control receive analgesic drug mefenamic acid 500 mg. Sore was measured by the VDS. Statistical test using unpaired t.Results: On the first day until the seventh day, p <0.001 for p <0.05, the author conclude there is a meaningful or significantdifference. gender, age, education, and experience on the extraction has no effect of VDS score or not a confounding variable, p> 0.05.Conclusions: There are significant differences the scores VDS of sore post odontektomi between the group treated with etoricoxib 90 mg and 500 mg mefenamic acid group. Gender, age, education, and experience has no effect on the extraction of VDS scores.